Indonesian Stock Market Reaction to the Escalation of the 2026 Iran Conflict: Evidence from an Event Study of Energy Sector Firms - Nidrah; Rika Kurniawati; Mufidatul Azmi (Economics and Business Journal (ECBIS), 2026)
This study examines the reaction of the Indonesian capital market to the escalation of the Iran conflict in 2026 using an event study approach focusing on energy sector firms listed on the Indonesia Stock Exchange. Market reactions are measured using Average Abnormal Return (AAR) and Trading Volume Activity (TVA). The observation period includes an 11-day event window (t−5 to t+5) and a 100-day estimation period. Statistical tests employed include the Shapiro–Wilk normality test, one-sample t-test, paired sample t-test, and Wilcoxon Signed Rank Test. The findings indicate that abnormal returns are only significant around the event date but do not differ significantly between pre- and post-event periods. In contrast, trading volume activity shows consistent and significant changes. These results suggest that geopolitical conflict information is more strongly reflected in trading behavior than in price adjustments. This study contributes to the literature by providing sector-specific evidence from an emerging market and highlighting behavioral market responses.